Cryptocurrency dan Stabilitas Sistem Keuangan: Tinjauan Literatur Dampak, Peluang, dan Tantangan Regulasi - Abdurohim, Abdurohim; Irfan, Mohamad (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2024)
Cryptocurrency has become a transformative element in modern financial systems, presenting significant opportunities and risks to systemic stability. Its rapid adoption, driven by blockchain technology, demonstrates potential for enhancing transparency and efficiency. However, challenges such as price volatility, regulatory gaps, and cybersecurity threats persist as critical concerns. This study addresses the dual role of cryptocurrency in fostering innovation while posing risks to global financial stability. Employing a systematic literature review, it analyzes academic articles from leading databases, including Scopus and Web of Science, focusing on recent studies (2018–2023) examining the security, regulation, and ethical dimensions of cryptocurrency and blockchain technology. Findings highlight cryptocurrency’s potential to improve financial inclusion and operational efficiency but underscore significant risks due to price instability and inadequate regulatory frameworks. Blockchain technology offers improved security and accountability; however, effective integration requires adaptive regulations and international cooperation. This study contributes by synthesizing insights into cryptocurrency’s systemic implications, bridging gaps in understanding the intersection of technology, regulation, and stability. It provides actionable recommendations for policymakers, financial institutions, and academics to develop balanced regulatory frameworks that support innovation while safeguarding consumer interests and financial stability. Holistic regulatory approaches, strengthened cybersecurity, and cross-sector collaboration are imperative for responsible cryptocurrency integration into global financial ecosystems.